(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2018)
The Biginelli one - pot three-component cyclocondensation was applied to prepare 3, 4 - dihydropyrimidin - 2 (1H) – ones from aldehydes, β-dicarbonyl compounds and urea (or thiourea) using ZnCl2 as a catalyst. The method offers several advantages including short reaction times and easy experimental work up procedures. Bangladesh J. Sci. Ind. Res.53(4), 327-332, 2018